Effects of voluntary exercise on the viability, proliferation and BDNF levels of bone marrow stromal cells in rat pups born from morphine- dependent mothers during pregnancy. (10th November 2016) - Haydari, Sakineh; Safari, Manouchehr; Zarbakhsh, Sam; Bandegi, Ahmad Reza; Miladi-Gorji, Hossein
Highlights: The role of morphine dependence during pregnancy on the viability of the bone marrow stromal cells is unknown. Maternal morphine administration increased the viability of the bone marrow stromal cells in rat pups. Maternal exercise increased the viability and BDNF levels of the bone marrow stromal cells in rat pups. Abstract: This study was designed to investigate whether free access to a running wheel during pregnancy in morphine-dependent mothers would influence the viability, proliferation and BDNF levels of bone marrow stromal cells in rat pups. Pregnant rats were made dependent by chronic administration of morphine in drinking water simultaneously with free access to a running wheel. Male pups are weaned at 21 days of birth and their bones marrows were aspirated from the femurs and tibias and also the bone marrow stromal cells (BMSCs) cultured. MTT assay was used to determine cell viability and proliferation rate. The level of BDNF was measured in the supernant of BMSCs culture by ELISA. The sedentary morphine-dependent mothers' pups showed a significant increase in the percentage cell viability and proliferation rate and also a significant decrease in the BDNF protein levels in BMSCs. The rat pups borne from exercising the control and morphine-dependent mothers exhibited an increase in the percentage viability, proliferation rate and BDNF levels of the BMSCs. This study showed that maternal exercise during pregnancy in morphine-dependent and non-dependent mothers, with increasing of BDNF levels increased the proliferation and viability of BMSCs in the rat pups. Also, chronic administration of morphine during pregnancy was able to increase the proliferation and viability of BMSCs in the rat pups.